Analysis of the SARS-CoV-2 envelope (E), nucleocapsid (N), and non-structural protein12 (nsp12) genes from COVID-19 patients in West Java - Azzania Fibriani; Irin Annisa Evitayani; Gusti Ayu Prani Pradani; Rebecca Stephanie; Ema Rahmawati; Ryan Bayusantika Ristandi; Cut Nur Cinthia Alamanda; Rifky Waluyajati Rachman; Rini Robiani; Isak Solihin (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2021)
According to World Health Organization, as of January 2021, Indonesia is the only Southeast Asian country in which COVID-19 is still occurring in community transmission. West Java is one of the provinces holding the highest positive cases number. With the envelope (E), nucleocapsid (N), and non-structural protein 12 (nsp12) being the target genes of SARS-CoV-2 diagnostic kits and several antiviral drugs, the study of genetic variations has become relevant and greatly important. Out of 267 oro-nasopharyngeal swab specimens that were previously confirmed positive for COVID-19 in qPCR diagnostic test in Laboratorium Kesehatan Provinsi Jawa Barat, ten samples with acceptable qualities were selected and three samples were sequenced using Sanger sequencing. Nonsynonymous mutations were observed in the envelope gene (L21F) and in the nucleocapsid genes (R203K, G204R, A211S, and S193I). Phylogenetic analysis showed that samples were clustered with other sequences carrying identical mutations, but clustered non-discriminatively with all sequences when carrying no mutation. No pattern in geographical areas and clades, except for R203K-G204R for being a marker for the GR clade. Protein structure analysis showed that mutations observed did not change the hydrophobicity and the secondary structure of the nucleocapsid, while stability change (ΔΔG) showed that all mutations, aside from the R203K-G204R, have neutral effect on the protein stability. Therefore, it can be concluded that mutations observed in this experiment did not impart preference to disperse in certain geographical areas or cause any significant structural change in the protein.